Gestão de resíduos de equipamentos eletroeletrônicos em município de médio porte no contexto da Legislação Ambiental - Oliveira, Maria Albiege Sales de (2018)
In the last two decades, innovation and competitiveness have been the key factors driving the technological development of electronic equipment. Higher speeds, an aggressive marketing, smaller form factors, higher performance and lower costs stimulate consumers to replace existing and still functional equipment by new models, at an increasingly higher rate. This early replacement leads to a massive obsolescence of electronic equipment, the so-called E-waste (WEEE). It occurs worldwide and has become a major environmental problem. E-waste often contains heavy metals (such as Lead, Cadmium, Beryllium, Arsenic, etc.), precious metals (Gold, Silver, Platinum, etc.) but also chlorinated products and flame-retardants. Some of these products become highly toxic when incinerated or slowly release toxic substances when dumped into landfill, causing immediate and irreversible impact on the environment and hence, to the human health. The main objective of this research was to analyze the management of WEEE in the city of Campina Grande-PB, located in the Northeast of Brazil, in relation to what proposes the Municipal Legislation, Complementary Law 087/2014, as well as the principles and guidelines established by the National Policy on Solid Waste, Law 12.305 / 2010. To achieve this objective, a qualitative exploratory study was carried out, seeking out ways to obtain greater familiarity with the problem at hand, involving a bibliographical survey of federal, state and municipal laws related to solid waste policies in Brazil as well about WEEE matters. To add quantitative data to the research, a field survey was conducted between march and november 2017, among residential consumers, shopkeepers of electrical and electronic equipment of the city of Campina Grande and local municipal bodies responsible for solid waste management. The research revealed that the Management of Waste of Electrical and Electronic Equipment in the city of Campina Grande is not in accordance with the guidelines of the Municipal Legislation, Complementary Law 087/2014, nor does it observe the principles established by the National Policy on Solid Waste, established by Law 12,305 / 2010.